The natural resources trap private investment without public commitment (Cambridge MIT Press, 2010)
Volatility in commodity prices has been accompanied by perpetual renegotiation of contracts between private investors in natural resource production and the governments of states with mineral and energy wealth. When prices skyrocket, governments want a larger share of revenues, sometimes to the point of nationalization or expropriation; when prices fall, larger state participation becomes a burden and the private sector is called back in. Recent and newsworthy changes in the price of oil (which fell from an all-time high of
Includes bibliographical references and index
Keywords: Natural resources -Government policy